2021
DOI: 10.3390/ijms222011205
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding-RNA-Mediated Regulation in Response to Macronutrient Stress in Plants

Abstract: Macronutrient elements including nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), and sulfur (S) are required in relatively large and steady amounts for plant growth and development. Deficient or excessive supply of macronutrients from external environments may trigger a series of plant responses at phenotypic and molecular levels during the entire life cycle. Among the intertwined molecular networks underlying plant responses to macronutrient stress, noncoding RNAs (ncRNAs), mainly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 134 publications
(155 reference statements)
0
6
0
Order By: Relevance
“…Moreover, miRNAs, as noncoding RNAs also play a key role in regulating poplar root responses to different N forms (Zhou and Wu, 2022a). CircRNAs, as another noncoding RNA, exist widely in different tissues of plants and play a key role in plant regulation of growth and development and resistance to abiotic stress (Zhang et al, 2020;Huang et al, 2021;Li et al, 2021;Ma et al, 2021). However, circRNAs in poplar root responses to different N forms have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miRNAs, as noncoding RNAs also play a key role in regulating poplar root responses to different N forms (Zhou and Wu, 2022a). CircRNAs, as another noncoding RNA, exist widely in different tissues of plants and play a key role in plant regulation of growth and development and resistance to abiotic stress (Zhang et al, 2020;Huang et al, 2021;Li et al, 2021;Ma et al, 2021). However, circRNAs in poplar root responses to different N forms have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Non-coding RNA (ncRNA) refers to RNAs that are not translated into proteins, mainly including microRNA (miRNAs), long non-coding RNA (lncRNA), and circular RNA (circRNA) [ 5 , 6 ]. They are transcribed from the genome but not translated into proteins, and perform their respective biological functions at the RNA level [ 7 ]. NcRNAs bind to many molecular targets to form regulatory networks, which in turn initiate specific cellular biological responses, with the function of regulating gene expression, influencing intracellular signaling, participating in epigenetic modifications and other life activities, and thus playing a role in the occurrence and development of tumors and other diseases [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…miR156 is a pivotal regulator for plant growth and development with pleiotropic effects. Several studies reported that miR156 is not only a key player in modulating a series of plant developmental processes such as branching, early flowering, fruit ripening, and cell proliferation but also in responses to environmental nutritional stresses by interaction with its targets, the SPL gene family [32][33][34][35] . Here we demonstrated for the first time, that overexpression of soybean homolog of miR156 in Arabidopsis could directly enhance the tolerance to P deficiency and seed yield under P deficit conditions, which is valuable for the development of efficient P-use soybean varieties in the future.…”
Section: Discussionmentioning
confidence: 99%